Radionuclides measured on three sediment cores from the Weddell Sea, Antarctica, supplementary data to: Frank, Martin; Eisenhauer, Anton; Bonn, Wolfgang J; Walter, Peter; Grobe, Hannes; Kubik, Peter W; Dittrich-Hannen, Beate; Mangini, Augusto (1995): Sediment redistribution versus paleoproductivity change: Weddell Sea margin sediment stratigraphy and biogenic particle flux of the last 250,000 years deduced from 230Thex, 10Be and biogenic barium profiles. Earth and Planetary Science Letters, 136(3-4), 559-573 - Frank, Martin; Eisenhauer, Anton; Bonn, Wolfgang J (PANGAEA - Data Publisher for Earth & Environmental Science, 1995)
High resolution 230Thex and 10Be and biogenic barium profiles were measured at three sediment gravity cores (length 605-850 cm) from the Weddell Sea continental margin. Applying the 230Thex dating method, average sedimentation rates of 3 cm/kyr for the two cores from the South Orkney Slope and of 2.4 cm/kyr for the core from the eastern Weddell Sea were determined and compared to delta18O and lithostratigraphic results. Strong variations in the radionuclide concentrations in the sediments resembling the glacial/interglacial pattern of the delta18O stratigraphy and the 10Be stratigraphy of high northern latitudes were used for establishing a chronostratigraphy. Biogenic Ba shows a pattern similar to the radionuclide profiles, suggesting that both records were influenced by increased paleoproductivity at the beginning of the interglacials. However, 230Thex0 fluxes (0 stands for initial) exceeding production by up to a factor of 4 suggest that sediment redistribution processes, linked to variations in bottom water current velocity, played the major role in controlling the radionuclide and biogenic barium deposition during isotope stages 5e and 1. The correction for sediment focusing makes the 'true' vertical paleoproductivity rates, deduced from the fluxes of proxy tracers like biogenic barium, much lower than previously estimated. Very low 230Thex0 concentrations and fluxes during isotope stage 6 were probably caused by rapid deposition of older, resedimented material, delivered to the Weddell Sea continental slopes by the grounded ice shelves and contemporaneous erosion of particles originating from the water column.
This dataset is supplement to doi:10.1016/0012-821X(95)00161-5
Keywords: Datensammlung